Democratic party in Peru: There is no first without second! - Huamanchumo de la Cuba, Luis E. (2008)
This paper presents a theoretical exercise to obtain the maximum number of candidates to be submitted to presidential elections to avoid a second round. The method used to achieve this goal is to obtain the probability density function of the number of candidates from the average of the ratios of the political preference share, establishing the likelihood that someone to be elected president in the first round on 1%.